ANALYSIS OF STANDARD EXPENDITURE (ASB) IN SUPPORTING THE PROCESS OF PLANNING, BUDGETING, AND MONITORING REGIONAL BUDGETS OF MEDAN CITY GOVERNMENT - Hazmanan Khair; Satria Tirtayasa (CERED Indonesia Institute, 2021)
The aims of this research are to provides guidelines for carrying out budget preparation and to provide benchmarks for assessing budget execution performance. As for the research scope, was all the Local Government Unit of Work (SKPD) under the Medan City Government. The target of this research is all non-physical activities that are financed by direct expenditure of the Medan City Government APBD for the 2018 Fiscal Year. Data collection is carried out by asking all work units, especially work units that perform non-physical work to submit data related to work that has never been carried out or become their authority to become raw materials for the preparation of non-physical ASB. Data analysis includes the data collection stage, the editing stage, the data tabulation stage, and the data description stage, namely the frequency table or diagram, the central tendency size, the dispersion measure to understand the characteristics of the research sample data. The result of this research was from 25 types of training that were sampled it can be concluded that 16 types of training are efficient while 9 others are inefficient.